1988
DOI: 10.1021/ma00180a006
|View full text |Cite
|
Sign up to set email alerts
|

Microtacticity distribution of polypropylenes prepared with heterogeneous Ziegler-Natta catalysts

Abstract: Polypropylenes produced with various heterogeneous titanium-based Ziegler-Natta catalysts were fractionated by solvent extraction technique. The infrared analysis of the fractions indicates the presence of a crystalline syndiotactic sequence, soluble in xylene at 20"C, and boiling hexane soluble fractions of all samples examined. Highly syndiotactic polypropylene (proportion of rrrr pentad is 0,50), comparable in syndiotacticity to the syndiotactic polymer prepared at -78 "C with a homogeneous vanadium catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…TREF analysis of polypropene prepared with MgCl 2 -supported catalysts has been already reported by many research groups [1][2][3][4][5][6]33) . Kakugo et al pointed out that there exists a bimodal tacticity distribution between 93% and 98% in the pentad level in fractions eluted above 100 8C for the polymer with a catalyst system involving an electron donor, suggesting that at least two types of active species are present in the system 1) .…”
Section: Comparison Of Tacticity Distributions Of Polypropenes Obtainmentioning
confidence: 76%
See 2 more Smart Citations
“…TREF analysis of polypropene prepared with MgCl 2 -supported catalysts has been already reported by many research groups [1][2][3][4][5][6]33) . Kakugo et al pointed out that there exists a bimodal tacticity distribution between 93% and 98% in the pentad level in fractions eluted above 100 8C for the polymer with a catalyst system involving an electron donor, suggesting that at least two types of active species are present in the system 1) .…”
Section: Comparison Of Tacticity Distributions Of Polypropenes Obtainmentioning
confidence: 76%
“…Kakugo et al pointed out that there exists a bimodal tacticity distribution between 93% and 98% in the pentad level in fractions eluted above 100 8C for the polymer with a catalyst system involving an electron donor, suggesting that at least two types of active species are present in the system 1) . Furthermore, Kioka et al demonstrated that polypropenes have a broad and continuous distribution of tacticity and the addition of an electron donor drastically reduces the amount of atactic and low isotactic polypropene, resulting in a very sharp tacticity distribution 6) .…”
Section: Comparison Of Tacticity Distributions Of Polypropenes Obtainmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of more than one isospecific active site agrees with the results of Kakugo. 10 Since internal electron donors influence the tacticity distributions of PPs, one may conclude that internal electron donors can convert aspecific active sites into two isospecific active sites and internal electron donors are present in the environment of isospecific active sites. However, the conversion of aspecific active sites into isospecific ones varies with the internal electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…2 , 3 Ester compounds, as weak Lewis bases, have also been used in ionic polymerization systems as the third initiator component. Cationic polymerization of isobutyl vinyl ether (IBVE) with !BVE-acetic acid adduct/EtAICl 2 in the presence of ester additive, such as ethyl acetate and ethyl benzoate, proceeds in a living manner, while in the absence of the Lewis base neither living nor long-lived propagating species are formed under the same conditions.…”
Section: Living Polymerization Imentioning
confidence: 99%